Terrorism as a Transnational Crime that Threatens Indonesia - Marzio, Aldy (Security Intelligence Terrorism Journal (SITJ), 2024)
This paper aims to (1) analyze Indonesia's vulnerability against terrorism; and (2) analyze efforts to counter-terrorism in Indonesia. In compiling this paper, the author collected secondary data in the form of written documentaries, namely mass media articles, journal articles and relevant books. The study results indicate that terrorism is a transnational crime with a major threat to the nation and state. In Indonesia there have been several acts of suicide bombing terrorism in the name of religious teachings. Suicide bomb terrorists consider this to be a sacred duty that is obligatory and of great benefit to their group. Indonesia's vulnerability to terrorism is determined by demographic, geographic, economic and ideological factors. Advances in information and communication technology and the increase in the number of internet users in Indonesia can also provide opportunities for cyberterrorism to occur. In carrying out counter-terrorism, the Indonesian government implements pre-emptive, preventive and repressive efforts. One of the counter-terrorism programs that raises pros and cons in Indonesian society is the involvement of the TNI. According to the author, the TNI should only be involved in counter-terrorism assistance if the National Police and BNPT experience difficulties or obstacles. A military counter-terrorism approach has the potential to violate human rights, especially against parties who are merely suspected of having been exposed to radical ideology.